1970
DOI: 10.3329/akmmcj.v3i1.10108
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Uterine Scar on Repeat Second Cesarean Section in Patients with Previous Cesarean Section

Abstract: only marginally increased among women undergoing a trial of labor 2 than among those undergrant an elective repeat cesarean section (0.4% vs 0.2% OR=2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…and co-workers at Gujarat among 385 women, and Nargis N. et al among 570 women at Dhaka. 14,15 In our study, RCS was done in six women where no scar dehiscence or rupture was noted similar to the study from Ludhiana, India by Puri P. and co-workers. 16 There was high risk of morbidly adherent placenta in women with low lying placenta and previous section, so planned antepartum and intrapartum assessment is mandatory to prevent maternal mortality and morbidity.…”
Section: Discussionsupporting
confidence: 61%
“…and co-workers at Gujarat among 385 women, and Nargis N. et al among 570 women at Dhaka. 14,15 In our study, RCS was done in six women where no scar dehiscence or rupture was noted similar to the study from Ludhiana, India by Puri P. and co-workers. 16 There was high risk of morbidly adherent placenta in women with low lying placenta and previous section, so planned antepartum and intrapartum assessment is mandatory to prevent maternal mortality and morbidity.…”
Section: Discussionsupporting
confidence: 61%
“…Thus some women with scar complications did not present with scar tenderness. 14 Rubina et al in a study of 120 women found three cases of scar tenderness of which one had a ruptured uterus at cesarean. 15 The only other study that was available was one of 99 women, where 1 woman had scar tenderness with intact scar while one case of dehiscence of scar did not have scar tenderness.…”
Section: Discussionmentioning
confidence: 97%
“…A group of investigators concluded that among women with a previously scarred uterus, induction of labour is associated with an increased risk of rupture uterus compared with spontaneous labour (2.3% vs 0.7% p=0.001). 2 The present study was done to know the maternal and fetal outcome in patients with previous cesarean section and those required repeat CS.…”
mentioning
confidence: 99%